Strategy, Diplomacy, Humanity : Life and Work of Sahabzada Yaqub-Khan - Compiled, Edited, Introduced by Anwar Dil (Islamabad International Forum Takshila Research University, 2005)
Lectures of an Ex-Foreign Minister of Pakistan; includes his brief life sketch.
Includes Index and Illustrations
Keywords: Pakistan -- Diplomatic Relations